Examining the influence of health sector coordination on the efficiency of county health systems in Kenya - Lizah Nyawira; Rebecca G Njuguna; Benjamin Tsofa; Anita Musiega; Joshua Munywoki; Kara Hanson; Andrew Mulwa; Sassy Molyneux; Isabel Maina; Charles Normand; Julie Jemutai; Edwine Barasa (BMC, 2023)
Abstract Background Health systems are complex, consisting of multiple interacting structures and actors whose effective coordination is paramount to enhancing health system goals. Health sector coordination is a potential source of inefficiency in the health sector. We examined how the coordination of the health sector affects health system efficiency in Kenya. Methods We conducted a qualitative cross-sectional study, collecting data at the national level and in two purposely selected counties in Kenya. We collected data using in-depth interviews (n = 37) with national and county-level respondents, and document reviews. We analyzed the data using a thematic approach. Results The study found that while formal coordination structures exist in the Kenyan health system, duplication, fragmentation, and misalignment of health system functions and actor actions compromise the coordination of the health sector. These challenges were observed in both vertical (coordination within the ministry of health, within the county departments of health, and between the national ministry of health and the county department of health) and horizontal coordination mechanisms (coordination between the ministry of health or the county department of health and non-state partners, and coordination among county governments). These coordination challenges are likely to impact the efficiency of the Kenyan health system by increasing the transaction costs of health system functions. Inadequate coordination also impairs the implementation of health programmes and hence compromises health system performance. Conclusion The efficiency of the Kenyan health system could be enhanced by strengthening the coordination of the Kenyan health sector. This can be achieved by aligning and harmonizing the intergovernmental and health sector-specific coordination mechanisms, strengthening the implementation of the Kenya health sector coordination framework at the county level, and enhancing donor coordination through common funding arrangements and integrating vertical disease programs with the rest of the health system. The ministry of health and county departments of health should also review internal organizational structures to enhance functional and role clarity of organizational units and staff, respectively. Finally, counties should consider initiating health sector coordination mechanisms between counties to reduce the fragmentation of health system functions across neighboring counties.